2015
DOI: 10.1111/bjet.12279
|View full text |Cite
|
Sign up to set email alerts
|

Methodological approaches in MOOC research: Retracing the myth of Proteus

Abstract: This paper explores the methodological approaches most commonly adopted in the scholarly literature on Massive Open Online Courses (MOOCs), published during the period January 2008-May 2014. In order to identify trends, gaps and criticalities related to the methodological approaches of this emerging field of research, we analysed 60 papers selected across four relevant scientific databases plus one journal in the sector of e-learning that published a special issue on this topic. The emerging picture is that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 43 publications
3
80
1
4
Order By: Relevance
“…Besides, there is an increasing interest from lifelong learners, higher education institutions and for-profit platforms from 2012 onwards, which is also visualized in the Google trends for MOOCs (Figure 2). This pattern is quite similar to those reported by Liyanagunawardena et al (2013), Ebben and Murphy (2014), Sa'don et al (2014) and Raffaghelli et al (2015). Since 2012, MOOC pedagogy has gotten increased attention with clear indications for its big impact on lifelong learning as concluded in the consequent Innovation Reports from the Open University, UK (Sharples et al, 2012;2014).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Besides, there is an increasing interest from lifelong learners, higher education institutions and for-profit platforms from 2012 onwards, which is also visualized in the Google trends for MOOCs (Figure 2). This pattern is quite similar to those reported by Liyanagunawardena et al (2013), Ebben and Murphy (2014), Sa'don et al (2014) and Raffaghelli et al (2015). Since 2012, MOOC pedagogy has gotten increased attention with clear indications for its big impact on lifelong learning as concluded in the consequent Innovation Reports from the Open University, UK (Sharples et al, 2012;2014).…”
Section: Introductionsupporting
confidence: 84%
“…While theses and dissertations used qualitative (49%), quantitative (21%), mixed (18%), review (8%) and other (4%) research methodologies (Table 1), Gasevic et al (2014) reported that of all the research submissions to MOOC Research Initiative (N = 78), 42% was mixed, 33% was quantitative and 24% was qualitative. Raffaghelli et al (2015) also reported that of all the articles they examined, 20% was mixed, 15% was quantitative and 12% was qualitative studies, 30% was theoretical-conceptual, 15% was not clear (in research design) and 8% was design based research. Looking at the research model/design, the following frequencies occur (N = 51): case study is the most used research model (31%), followed by the correlational research model (14%), literature review (8%), explanatory design (6%), exploratory design (6%) and convergent parallel design (6%).…”
Section: Figure 5: Research Themes Of Theses and Dissertationsmentioning
confidence: 99%
“…The 21 st century witnessed an educational paradigm shift, stemming from the widespread use of (Weller, 2014): It is suggested There have been some efforts in academia to understand and analyse the MOOC phenomenon; several papers have examined MOOC research in academic journals (Ebben & Murphy, 2014;Gasevic, Kovanovic, Joksimovic, & Siemens, 2014;Kennedy, 2014;Liyanagunawardena et al, 2013;Raffaghelli, Cucchiara, & Persico, 2015;Sa'don, Alias, & Ohshima, 2014;Sangrà, González-Sanmamed, & Anderson, 2015;Veletsianos & Shepherdson, 2015Bozkurt, Akgün-Özbek, & Zawacki-Richter, 2017). These papers examined aspects of MOOC research such as methodology, pedagogy, and theory.…”
Section: Introductionmentioning
confidence: 99%
“…Online video lectures are becoming a main component of online learning within formal courses and informal learning environments, such as Massive Open Online Courses (MOOCs) (Daniel, 2012;Kalman, 2014;Raffaghelli, Cucchiara, & Persico, 2015;Siemens, Gašević, & Dawson, 2015). Online video lectures have been successfully used for supporting face-to-face learning (Boton & Gregory, 2015;Brecht, 2012;Kinash, Knight, & McLean, 2015;Whatley & Ahmad, 2007;Wieling & Hofman, 2010), as well as in-class learning, e.g., when there is a need to show students visual elements (Ostashewski, Reid, & Ostashewski, 2016).…”
Section: Introductionmentioning
confidence: 99%